1969
DOI: 10.1302/0301-620x.51b4.604
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Pseudarthrosis of the Tibia

Abstract: 1. Three cases of infantile pseudarthrosis of the tibia treated successfully by delayed autogenous by-pass graft are reported. 2. The delayed autogenous graft is stouter, stronger and more easily handled and has enhanced osteogenic properties than a graft transferred immediately. 3. The by-pass graft commends itself, firstly, because it does not disturb the pseudarthrosis, which in consequence helps the immobilisation of the graft; secondly, because it is well embedded in healthy bone above and below, well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…At the same time, he also clarified that the cause of CPT is a mechanical reason, emphasizing the use of plaster after the operation and suggesting delaying the operation to 18 months of age. 15 After that, Lloyd-Roberts and Shaw, 22 Eyre-Brook et al, 23 and Baw 24 respectively reported 18 cases treated with the McFarland method with a total of 12 unions in tibias and two amputations. In 1981, Morrissy et al 18 reported a series of total 40 cases, of which 7 underwent prophylactic bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, he also clarified that the cause of CPT is a mechanical reason, emphasizing the use of plaster after the operation and suggesting delaying the operation to 18 months of age. 15 After that, Lloyd-Roberts and Shaw, 22 Eyre-Brook et al, 23 and Baw 24 respectively reported 18 cases treated with the McFarland method with a total of 12 unions in tibias and two amputations. In 1981, Morrissy et al 18 reported a series of total 40 cases, of which 7 underwent prophylactic bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Bone graft incorporation depends on many factors of which graft stability and recipient bed are crucial. 2 Would they describe the technique they used for graft stability? What proportion of grafts were sutured as opposed to slotted?…”
mentioning
confidence: 99%